The missing link: Bringing institutions back into the debate on economic globalisation - Marie-Laure Djelic; Sigrid Quack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
In der Auseinandersetzung mit der Globalisierung von Wirtschaftsprozessen kann sich die sozialwissenschaftliche Institutionentheorie nicht mehr auf die Untersuchung nationaler Konfigurationen beschränken, sondern sollte der transnationalen Rekombination institutioneller Arrangements mehr Aufmerksamkeit schenken. Für die Untersuchung solcher Prozesse sind veränderte analytische Werkzeuge erforderlich. Die Autorinnen dieses Beitrags schlagen eine Synthese von "National Business Systems-" und "Varieties of Capitalism-" Ansätzen mit kulturalistischen und phänomenologischen Varianten der Institutionentheorie vor. Es werden drei Aspekte der institutionellen Analyse vertieft, die zu einem besseren Verständnis des Verhältnisses von Globalisierung und Institutionen beitragen: Institutionalisierung als Prozeß, Rekombination als Mechanismus der Institutionengenese und des Institutionenwandels und eine Mehrebenenanalyse des Zusammenspiels von institutionellen Veränderungen auf nationaler und transnationaler Ebene. Die vorgeschlagene Synthese verschiedener institutionalistischer Ansätze bietet einerseits Ansatzpunkte für die Untersuchung der Rolle nationaler Akteure in der Genese und Entwicklung transnationaler Institutionen. Andererseits trägt sie zu einem besseren Verständnis der Rekombination von Elementen verschiedener institutioneller Arrangements sowie der Herausbildung neuer Institutionen auf transnationaler Ebene bei. Diese Entwicklungen im transnationalen Raum wirken wiederum auf Institutionen in nationalen Sozial- und Wirtschaftsräumen ein. Die Autorinnen des vorliegenden Beitrages argumentieren, daß die Abfolge und Kombination einer Reihe gradueller und zunächst geringfügiger Veränderungen über einen längeren Zeitraum hinweg zu einem signifikanten Wandel von gesellschaftlichen Institutionen führen können. – – Faced with ongoing debates on globalisation, societal institutionalism in its traditional form is showing its limits. In this paper, we suggest that a serious sociologically grounded and institutional contribution to the ongoing debate on global governance calls for a shift in focus - away from the preoccupation with national configurations and towards an attempt at understanding transnational recombinations. The investigation of transnational recombination calls for new analytical tools. Here we argue that the solution may come from an hybridisation of NBS and VOC approaches with other variants of the institutionalist argument in particular those we label 'cultural' or 'phenomenological'. We elaborate on three aspects of institutional analysis that we identify as key to getting a better understanding of the relationship between globalisation and institutions. Firstly, we propose an interpretation of institutionalisation as a process and not a state of things. Secondly, we reinterpret institutional genesis and institutional change as revealing recombination. Thirdly, we argue for a more systematic analysis of the interplay of such processes of recombination across different levels of analysis, particularly the national and the transnational. With a conceptual framework so reformulated, it is possible to take in the transnational reality in its full complexity. We show, on the one hand, how the NBS and VOC perspectives are an interesting starting base to look at the structuration and stabilisation of the transnational reality. On the other hand, we gain new insights in the ways in which institution building and recombination at the transnational level become reflected - often progressively and somewhat incrementally - at the national business system level. Our proposition is that the succession and combination, over a long period of time, of a series of incremental and sometimes minor transformations could lead in the end to consequential and significant change.
Keywords: 330; Globalisierung; Institutionalismus; Regulierung; International; Ordnungspolitik; Welt